Innate immune components affect growth and virulence traits of bacterial-vaginosis-associated and non-bacterial-vaginosis-associated Gardnerella vaginalis strains similarly - Castro, Joana (2018)
Mucosal surfaces of the female reproductive tract contain a variety of antimicrobial components that provide the first line of defense against bacteria involved in the development of bacterial vaginosis (BV). Microbiological analysis of BV has shown Gardnerella vaginalis to be a prominent species in BV development. However, G. vaginalis colonization does not always lead to BV. Over the last decade, phenotypic and genotypic studies have demonstrated the existence of strain variants. Therefore, this study aimed to investigate if the major components of the vaginal immune response, specifically lysozyme, lactoferrin and Î²-defensin 2, differently affected virulence traits of G. vaginalis strains isolated from healthy women or from women with BV. Gardnerella vaginalis strains were first genotyped by the clade classification system and then phenotypically characterized. Our results revealed that key differences in initial adhesion existed among the isolates but that these differences could not be predicted using the clade-genotyping approach. Importantly, we found that growth, initial adhesion and biofilm formation were strongly affected by lysozymes, but at similar levels in both groups, suggesting that the response to host immune components is not a distinguishing characteristic of isolates from women with BV versus those from healthy women.